Effects of Slow-Release Trace Ni2+ Ceramsite on the Performance of Anaerobic Treatment of Wastewater - Su, Huidong; Shi, Dongling (Asian Journal of Chemistry, 2015)
The experimental load of Ni2+ to the adsorbent of ceramsite, making it release Ni2+ slowly, increasing the biological effective degrees of microscale metals element, improving the microbial treatment efficiency of organic wastewater.Using fly ash, cement, lime, gypsum as main raw material, CaCl2, Na2SO4 and NaCl as activating agent, using steam curing method, determine the best proportion of raw material, investigating the technological conditions.Discussing the release process of trace Ni2+ metal element of ceramsite. Through contrast test with the control group, homemade common ceramsite group, commodity ceramsite group and slow-release Ni2+ ceramsite group in the microbial reactor can obtain: the removal rate of COD is 72.8 %, 81.4 %, 81. 3 % and 91.8 % respectively, removal rate of adding modification ceramsite is the peak, 19 % higher than control group. Slow-release ceramsite can increase the activity of activated sludge,comparing with other ceramsite and adding trace metal element directly,which has more superior process performance.